2005
DOI: 10.1175/jcli3412.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Ocean’s Climate to Diapycnal Diffusivity in an EMIC. Part II: Global Warming Scenario

Abstract: The sensitivity of the ocean’s climate to the diapycnal diffusivity in the ocean is studied for a global warming scenario in which CO2 increases by 1% yr−1 for 75 yr. The thermohaline circulation slows down for about 100 yr and recovers afterward, for any value of the diapycnal diffusivity. The rates of slowdown and of recovery, as well as the percentage recovery of the circulation at the end of 1000-yr integrations, are variable, but a direct relation with the diapycnal diffusivity cannot be found. At year 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In addition, eddy processes within and north of the Antarctic Circumpolar Current result in southward along-isopycnal heat transport across the Antarctic Circumpolar Current in the mean climatological circulation state (Gregory, 2000;Wolfe et al, 2008). With increased surface warming, the along-isopycnal temperature gradient decreases, which reduces the efficiency of the southward eddy-mediated transport of heat, resulting in heat accumulating north of the Antarctic Circumpolar Current (process [4] in Figure 1; Gregory, 2000;Dalan et al, 2005;Morrison and Hogg, 2013;Morrison et al, 2016). While surface warming might not be strong enough yet to efficiently impact southward eddy-mediated transport of heat, this decreased eddy heat transport could become an important mechanism in future warming (Morrison et al, 2016).…”
Section: Mechanisms At Playmentioning
confidence: 99%
“…In addition, eddy processes within and north of the Antarctic Circumpolar Current result in southward along-isopycnal heat transport across the Antarctic Circumpolar Current in the mean climatological circulation state (Gregory, 2000;Wolfe et al, 2008). With increased surface warming, the along-isopycnal temperature gradient decreases, which reduces the efficiency of the southward eddy-mediated transport of heat, resulting in heat accumulating north of the Antarctic Circumpolar Current (process [4] in Figure 1; Gregory, 2000;Dalan et al, 2005;Morrison and Hogg, 2013;Morrison et al, 2016). While surface warming might not be strong enough yet to efficiently impact southward eddy-mediated transport of heat, this decreased eddy heat transport could become an important mechanism in future warming (Morrison et al, 2016).…”
Section: Mechanisms At Playmentioning
confidence: 99%
“…In the new IGSM2 the ocean component has been replaced by either a two-dimensional (latitude-longitude) mixed layer anomaly-diffusing ocean model (hereafter denoted as IGSM2.2) or a fully threedimensional ocean GCM (denoted as IGSM2.3). Dalan et al (2005b) showed that different versions of the 3D ocean model with different rates of heat uptake can be produced by changing the vertical-diapycnal diffusion coefficients. However, changing the diapycnal coefficient also alters the ocean circulation, in particular the strength of North Atlantic overturning (Dalan et al 2005a).…”
Section: Ocean Componentmentioning
confidence: 99%
“…Dalan et al (2005b) showed that different versions of the 3D ocean model with different rates of heat uptake can be produced by changing the vertical-diapycnal diffusion coefficients. However, changing the diapycnal coefficient also alters the ocean circulation, in particular the strength of North Atlantic overturning (Dalan et al 2005a). Unfortunately, it appears infeasible (certainly without changes to parameterizations in the 3D models) to vary the heat uptake over the full range consistent with observations during the twentieth century and at the same time maintain a reasonable circulation.…”
Section: Ocean Componentmentioning
confidence: 99%
“…However, Banks and Gregory (2006) show using a GCM that heat uptake can vary significantly due to changes in ocean circulation and stratification, and therefore cannot be viewed solely as a passive process. Additionally, several modeling studies have shown that high-latitude regions control the ocean heat uptake in anthropogenic warming scenarios, specifically highlighting the importance of the Southern Ocean processes (e.g., Manabe et al 1991;Gregory 2000;Huang et al 2003;Gnanadesikan et al 2005;Xie and Vallis 2012) and the North Atlantic and its meridional overturning circulation (MOC; e.g., Dalan et al 2005;Rugenstein et al 2013). …”
Section: Introductionmentioning
confidence: 99%